2022
DOI: 10.1021/acsaem.1c04084
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Monoxide with in Situ Grown Rutile TiO2 Nanothorns as a Heterostructured Job-Sharing Anode Material for Lithium-Ion Storage

Abstract: Developing high-performance anodes is highly desired to meet the recent ever-increasing demands for high-energy lithium-ion batteries (LIBs). Titanium dioxide (TiO2) shows extremely stable performance as an anode material in LIBs, but its intrinsic structural limit critically inhibits the full utilization of the TiO2 material. Herein, we report a uniquely integrated heterostructure of rutile TiO2 (r-TiO2) nanothorns grown in situ over a new porous and conductive cubic crystalline titanium monoxide (TiO) core. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
0
9
0
2
Order By: Relevance
“…successfully prepared the surface-defected TiO 2− x with surface oxygen deficiency through calcination at the melting point of Mg (650 °C) by varying the mole ratio of the anatase TiO 2 and Mg (RT- y , where RT indicates reduced TiO 2 and y is the mole ratio of Mg to TiO 2 ). 33 Key observations here showed that when the mole ratio was below the threshold value of 0.75 mole ratio, Mg only reacted at the surface of TiO 2 to generate a superficial TiO 2− x and MgO, leaving behind a core of unreacted TiO 2 (TiO 2 @TiO 2− x –MgO). The reaction follows; TiO 2 + Mg → TiO 2− x + x MgO (0 < x < 1).…”
Section: History and Properties Of Mgmentioning
confidence: 67%
See 2 more Smart Citations
“…successfully prepared the surface-defected TiO 2− x with surface oxygen deficiency through calcination at the melting point of Mg (650 °C) by varying the mole ratio of the anatase TiO 2 and Mg (RT- y , where RT indicates reduced TiO 2 and y is the mole ratio of Mg to TiO 2 ). 33 Key observations here showed that when the mole ratio was below the threshold value of 0.75 mole ratio, Mg only reacted at the surface of TiO 2 to generate a superficial TiO 2− x and MgO, leaving behind a core of unreacted TiO 2 (TiO 2 @TiO 2− x –MgO). The reaction follows; TiO 2 + Mg → TiO 2− x + x MgO (0 < x < 1).…”
Section: History and Properties Of Mgmentioning
confidence: 67%
“…In addition to high surface area, porosity provides important deposition sites for active metals and mass transfer channels which are highly necessary for catalysis. 33 Highly porous and shape-dependent materials have been successfully prepared for numerous energy applications by employing hard templates such as zeolites, 46 mesoporous silicas, 47 and some metal oxides. 48 However, the preparation processes associated with these hard templates are complicated and environmentally unfriendly, especially for the removal of silica, which requires corrosive HF or NaOH.…”
Section: History and Properties Of Mgmentioning
confidence: 99%
See 1 more Smart Citation
“…Li‐ion batteries are the frontrunner technology for high‐power and intermediate‐scale energy storage used in a broad range of applications, including electric vehicles and portable devices [1] . Anatase TiO 2 is a promising fast‐charging material for Li‐ion battery anodes with theoretical specific charge capacities competitive with those of graphite electrodes [2–8] . TiO 2 is abundant, inexpensive [6] and shows low volume changes (<4 %) during Li + (de)intercalation: [9] TiO2+xLi++xe-LixTiO2 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {{\rm T}{\rm i}{\rm O}}_{2}+{x{\rm L}{\rm i}}^{+}+{x{\rm e}}^{-}{\rm \ }{\stackrel{ {\rightarrow} } { {\leftarrow} } } {\rm \ }{{\rm L}{\rm i}}_{x}{{\rm T}{\rm i}{\rm O}}_{2}\hfill\cr}}$ …”
Section: Introductionmentioning
confidence: 99%
“…Li‐Ionen‐Batterien sind die führende Technologie für die Speicherung von Energie in hohem und mittlerem Umfang, die in einem breiten Spektrum von Anwendungen einschließlich Elektrofahrzeugen und tragbaren Geräten zum Einsatz kommt [1] . Anatas‐TiO 2 ist ein vielversprechendes, schnell aufladbares Material für Li−Ionen‐Batterieanoden mit theoretischen spezifischen Ladekapazitäten, die mit denen von Graphitelektroden konkurrieren können [2–8] . TiO 2 ist reichlich vorhanden, kostengünstig [6] und zeigt geringe Volumenänderungen (<4 %) während der Li + (De)Intercalation [9] .…”
Section: Introductionunclassified